STRATEGIC PLANNING IN A MODER N SCHOOL: EVALUATION ASPECT OF A REAL SITUATION - Gumuliauskienė, Aušrinė; Gricienė, Dalia (Acta Paedagogica Vilnensia, 2010)
Modern schools work in the context of rapid change, increasing dependence on the external environment and rising requirements to educational organisations. Significance of strategic school planning is first of all associated with the self-evaluation of a real situation, as this process determines reliability of the strategic plan in connection with the influence of political, economic, cultural, technical/technological and competitive factors on school and its internal potential. Content analysis of the strategic plans of general education schools allowed us to identify substantial peculiarities of the situation in schools. The research shows that today’s schools function in the conditions of intensifying influence of the external environment. Nowadays the most significant impact on schools is made by social and economic factors. Schools give more negative than positive opinion about the influence of the aforementioned factors and especially their subsequence on different fields of school activities. Not sufficient financial education support is considered as a main threat to schools and the subsequence of this process is seen as main weaknesses of the organisations. More than two thirds of schools with a stable situation analysis emphasize unfriendly social environment. All schools indicate unsatisfactory demographic situation leading to the decrease in the number of students and growing competition among schools as a main threat. School management, student support and human resources are the main strengths of schools allowing them to seek for the ways to connect them with external and internal influence groups and look for opportunities to develop them in other fields of school activities. Smaller amount of the statements reflecting schools opportunities in comparison with the external threats has been identified. This fact allows us to presume that today’s schools function in the excess conditions of external threats and negative influences, not always make adequate and complex evaluation of their potential opportunities in the external environment and link it with the systemic development of the organisation. Teachers’ qualification and its improvement system, project work, use of the active teaching methods, school work evaluation system and students achievements are the main fields where schools see the most considerable potential opportunities.